2021
DOI: 10.1038/s41598-021-97115-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory mechanism studies of ginseng leaves on lung cancer based on network pharmacology and molecular docking

Abstract: Panax ginseng is one of the oldest and most generally prescribed herbs in Eastern traditional medicine to treat diseases. Several studies had documented that ginseng leaves have anti-oxidative, anti-inflammatory, and anticancer properties similar to those of ginseng root. The aim of this research was to forecast of the molecular mechanism of ginseng leaves on lung cancer by molecular docking and network pharmacology so as to decipher ginseng leaves' entire mechanism. The compounds associated with ginseng leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…The data concerning the lowest binding energy resulting from molecular docking was obtained. The lower the binding energy, the stronger the binding force between the active ingredient and the target protein: a drug molecule with binding energy ≤ −5.0 kJ/mol is considered to have a good binding activity to the target ( Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The data concerning the lowest binding energy resulting from molecular docking was obtained. The lower the binding energy, the stronger the binding force between the active ingredient and the target protein: a drug molecule with binding energy ≤ −5.0 kJ/mol is considered to have a good binding activity to the target ( Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, for ginsenosides with too many targets, we only selected the top 20 targets associated with DM for subsequent analysis. The UniProt database ( https://www.uniprot.org/ ) was used to convert target protein names into target gene names to standardize gene names 17 , 18 .…”
Section: Methods and Analysismentioning
confidence: 99%
“…Next, the GeneCards (GeneCards, https://www.genecards.org/ ), the Online Mendelian Inheritance of Human Beings (OMIM, https://www.omim.org/ ), the Pharmacogenetics and Pharmacogenomics Database (PharmGkb, https://www.pharmgkb.org ), the Therapeutic Targets Database (TTD, http://db.idrblab.net/ttd/ ), and the Drugs and Drug Target Information Databases DM-related disease target genes (Drug Bank, https://go.drug/bank.com/ ) were integrated 18 . Finally, we used BioLadder ( https://www.bioladder.cn/web/#/pro/index ) to identify and visualise the intersecting targets of both ginsenosides and disease targets.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For the treatment of tumors, traditional Chinese medicine schemes have the advantages of low risk, high safety, and low price, and have been widely verified both theoretically and experimentally. It has been found that saffron, ginseng, and other traditional Chinese medicines have anti-tumor effects ( 12 , 13 ). The present study regarding the relationship between traditional Chinese medicine and GBM will assist in guiding the development of new drugs and improving the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%